2019
DOI: 10.1002/qre.2487
|View full text |Cite
|
Sign up to set email alerts
|

One‐sided runs‐rules schemes to monitor autocorrelated time series data using a first‐order autoregressive model with skip sampling strategies

Abstract: In some industrial or health-related processes, it makes more practical sense to monitor either an increase only or a decrease only in the quality characteristic of interest. Consequently, in this paper, we propose four one-sided Shewhart X charts supplemented with runs-rules to monitor the mean of autocorrelated normally distributed samples using a stationary first-order autoregressive model. To counteract the negative effect of autocorrelation, we implement a sampling strategy which involves sampling of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…It is worth mentioning that Equations (16) to (19), or similar versions, have been done in earlier and recent publications for the i.i.d. and autocorrelated observations scenarios using one-and two-sided schemes; see Page, 38 Champ, 39 Acosta-Mejia, 40 Lim and Cho, 42 Shongwe et al, 26,44 and Shongwe and Malela-Majika. 45 A number of authors have shown that if a monitoring scheme is designed based on one specific shift size δ, it would perform poorly when it is considerably different from the assumed one; see Reynolds and Lou 50 and Ryu et al 51 This makes the ARL inefficient in assessing the overall performance of a monitoring scheme.…”
Section: Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that Equations (16) to (19), or similar versions, have been done in earlier and recent publications for the i.i.d. and autocorrelated observations scenarios using one-and two-sided schemes; see Page, 38 Champ, 39 Acosta-Mejia, 40 Lim and Cho, 42 Shongwe et al, 26,44 and Shongwe and Malela-Majika. 45 A number of authors have shown that if a monitoring scheme is designed based on one specific shift size δ, it would perform poorly when it is considerably different from the assumed one; see Reynolds and Lou 50 and Ryu et al 51 This makes the ARL inefficient in assessing the overall performance of a monitoring scheme.…”
Section: Scenariomentioning
confidence: 99%
“…Some of these models are known as autoregressive (AR), moving average (MA), autoregressive moving average (ARMA), autoregressive integrated moving average (ARIMA), etc; see Box et al for more thorough discussion on these. In this paper, we only consider the well‐known first‐order AR model (ie, AR(1)) as a starting point (other models will be discussed in upcoming articles) and because according to Alwan and Radson, this is the most commonly used time series model in SPM applications; see also Wardell et al, Runger and Willemain, Claro et al, Kazemzadeh et al, Costa and Machado, Chang and Wu, Keramatpour et al, Franco et al, Hu and Sun, Osei‐Aning et al, Garza‐Venegas et al, Shongwe et al, Ahmad et al, etc, for additional indication that AR(1) is the most used model in SPM due to its simplicity as compared with other stationary time series processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is to sample from the observation data stream less frequently. [5][6][7][8] It seems to be an easy solution; however, it has the disadvantage of making a considerable amount of available data wasted. For example, if we sample every tenth observation, 90% of the information is discarded.…”
Section: Introductionmentioning
confidence: 99%
“…Polunchenko and Raghavan provided a comparative study of the cumulative sum (CUSUM) chart and the Shiryaev‐Roberts procedure for the nonasymptotic setting with correlated observations. Shongwe et al presented four one‐sided Shewhart‐ trueX¯ charts with runs‐rules to monitoring the mean of autocorrelated normally distributed samples under an AR(1) model. Shongwe and Malela‐Majika proposed two Shewhart‐ trueX¯ charts with w‐of‐w runs‐rules based on the skipping sampling strategy for an AR(1) model.…”
Section: Introductionmentioning
confidence: 99%